2004
DOI: 10.1007/s00134-003-2092-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient State Index (PSI) measures depth of sedation in intensive care patients

Abstract: As the high prediction probability and the analysis of paired comparisons suggest, PSI may be used to quantify the level of propofol/sufentanil sedation in ICU patients. Further studies are required to test whether these promising results can be verified for other drug combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…Th e PSI generated by the brain function monitor did not correlate to the RSS, as previously demonstrated in other studies (8,17,18). Many of those studies were done in intensive care unit settings, when there was no procedure that might stimulate the patient and cause contraction of the frontalis muscle adjacent to the EEG leads.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Th e PSI generated by the brain function monitor did not correlate to the RSS, as previously demonstrated in other studies (8,17,18). Many of those studies were done in intensive care unit settings, when there was no procedure that might stimulate the patient and cause contraction of the frontalis muscle adjacent to the EEG leads.…”
Section: Discussionmentioning
confidence: 59%
“…Once the values associated with ≥50% EMG were excluded, the relation between RSS and PSI became signifi cant. In light to moderate sedation, particularly during an intense procedure, it is diffi cult to reduce the EMG impact on an EEG monitor (18). While Matsuzaki and Tanaka (2004) showed a useable signal for the bispectral index, the fi lters for EMG may not be adequate to eliminate frontalis muscle activity during periodontal surgery and establish a reliable PSI in this range of sedation at all times (7).…”
Section: Discussionmentioning
confidence: 99%
“…A PSI less than 60 is considered deeply sedated, whereas a PSI of 60 or greater includes moderately to mildly sedated or alert/wake states. 17,19,22 The models contained fixed effects of before or after the event, time, and the interaction of the 2 and random effects of patient, time, and the interaction of time and before or after event by using an estimated spatial power covariance pattern for the within-subject variance and unstructured covariance pattern for between-subject variance. The spatial power covariance pattern takes into account the autocorrelation of the repeated measures of the individual event occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences have been documented between mean PSI values obtained during different sedation states. 15,16 Researchers in several studies [17][18][19][20] have compared PSI with subjective sedation tools and reported significant relationships between the PSI and these tools as well.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Schneider et al [8], in a study of surgical intensive care patients receiving Propofol and Sufentanil, found the PSI to be highly predictive of the depth of sedation in mechanically ventilated patients.…”
Section: Discussionmentioning
confidence: 99%